Pluralism in Science - Valevičius, Vytautas (Problemos, 1984)
The problem of plurality of scientific theories is being analysed. Proceeding from the analysis of structure of a theory the author of the article supposes two possible solutions, namely, cumulative, characteristic to neopositivism and pluralistic, found in the works of I. Lakatos, P. Feyerabend and some others. The ignorance of dialectics in the development of scientific theories is blamed for the deficiency of both extreme conceptions.